2011
DOI: 10.1108/09604521111113465
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of users and non‐users of banking self‐service technology in Portugal

Abstract: Purpose -The purpose of this paper is to examine the behaviour of Portuguese users and non-users of self-service technologies (SSTs) in banking services. Design/methodology/approach -An empirical study is conducted by means of a survey questionnaire. Data are collected from a sample of 300 respondents chosen to represent the Portuguese adult population in terms of age, gender, and geographical place of residence. Findings -The results show that Portuguese users of SST banking services are likely to be young to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…In order to measure the research structure the scales used by (Al-Hawari et al, 2009;Parasuraman et al, 1988;Proenca and Rodrigues, 2011) which have been utilized in devising some of the questions on the questionnaire. …”
Section: Methods and Instruments Applied For Data Gatheringmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to measure the research structure the scales used by (Al-Hawari et al, 2009;Parasuraman et al, 1988;Proenca and Rodrigues, 2011) which have been utilized in devising some of the questions on the questionnaire. …”
Section: Methods and Instruments Applied For Data Gatheringmentioning
confidence: 99%
“…Several authors have examined the relationship between satisfaction and service quality, particularly when this is influenced by new technologies (Al-Hawari et al, 2009;Bitner, Ostrom, & Meuter, 2002;Johns & Perrott, 2008;LaBarbera & Mazursky, 1983;Marr & Prendergast, 1993;Meuter et al, 2000;Nilsson, 2007;Proenca & Rodrigues, 2011;Shamdasani, Mukherjee, & Malhotra, 2008). Meuter et al, (2000) showed that satisfaction with SSTs is mainly related to the capacity to customise the service; in addition, a secondary benefit that contributes to customer satisfaction is the convenience of being able to produce and consume services when and where customers need them.…”
Section: Moderating Effects Of Self-service Technologies (Ssts)mentioning
confidence: 99%
See 2 more Smart Citations
“…Innovative technologies may gain a competitive edge and achieve higher production efficiency (Acharya, Kagan and Lingam, 2008). For banks, the use of service technologies enables significant cost reductions while enhancing service efficiency and effectiveness (Cronin, 2003;Proença and Rodrigues, 2011). Both aspects are related to banking solutions and bank efficiency.…”
Section: The Banking Technology Service Banking Solutions and Bank Ementioning
confidence: 99%